The European Union’s Approach to Artificial Intelligence from a Territorial Perspective: The Case of DIHs and EDIHs Programmes - Czyżewska-Misztal, Dorota (Europejskie podejście do sztucznej inteligencji z perspektywy terytorialnej na przykładzie programów DIH i EDIH, 2024)
Aim: The aim of the paper was twofold. Firstly, to identify and define the European Union’s approach to Artificial Intelligence from the territorial perspective. The main aim was achieved through a detailed analysis of the EU strategic documents evoking regional and urban aspects of AI. Secondly, the significance of Digital Innovation Hubs as a key AI European policy instrument was assessed In this paper, the author tried to answer the following research question: to what extent are the Digital Innovation Hubs a key policy instrument of the European Union’s approach to AI from a territorial perspective? Methodology: Literature review, desk research and text analysis (for EU strategic documents related to AI from the period 2018-onwards) are used as research methods in this paper. Results: The results show that the territorial dimension of AI, especially in the context of the EU strategic documents, has only been discussed to a limited extent. However, there are indeed some EU initiatives with a focus on AI, or to a large degree – their digital aspects. It is the case of Digital Innovation Hubs being an instrument to strengthen SMEs’ competitive position and boost their digital transformation combining a regional dimension. Implications and recommendations: The paper builds upon the growing importance of AI in different socio-economic contexts. However, in the EU strategic documents related to AI, this issue has been discussed only to a small extent. DIHs and EDIHs are indicated as a main tool of the EU policy to deploy digital services (and AI-related services specifically) to companies in a regional dimension. The paper suggests to continue assessing the importance of DIHs and especially EDIHs in this context. The challenge of digital transformation is huge for companies in the EU (according to the Digital Decade targets set for 2030 the AI take-up is 11% of enterprises in 2023 against 75% of enterprises targeted for 2030 (European Commission, 2023), and EDIHs are expected to be a main actor boosting this process in the EU context. Originality/value: The paper builds upon the territorial dimension of the EU’s approach to AI based on the EU strategic documents which is new in the literature. Moreover, it gives an extended overview of the DIHs and EDIHs programme in the context of AI, also suggesting fields for further research.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 2, s. 1-11
Keywords: digital transformation; Digital Innovation Hub; European Digital Innovation Hub; artificial intelligence; European Union; transformacja cyfrowa; hub innowacji cyfrowych; europejski hub innowacji cyfrowych; sztuczna inteligencja; Unia Europejska